2005
DOI: 10.1007/s00403-005-0613-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern and intensity of protoporphyrin IX induced by liposomal 5-aminolevulinic acid in rat pilosebaceous unit throughout hair cycle

Abstract: We have developed liposomal formulation of 5-aminolevulinic acid (ALA) to enhance topical delivery and examined ALA-induced protoporpyrin (PpIX) expression in rat pilosebaceous unit throughout hair cycle. Two types of liposomes--glycerol dilaulate (GDL) and phosphatidylcholine (PC)--were formulated and both liposomal ALA increased PpIX expression in rat dorsal skin and pilosebaceous units when compared with free ALA. However, iontophoresis combined with liposomal ALA reduced the expression intensity of PpIX in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Previously, Han et al also reported that transfollicular delivery of drug molecules was enhanced by using a combination of liposomes and iontophoresis (Han et al, 2005;Han et al, 2004). In those reports, the intrafollicular delivery of small fluorescent drug molecules was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Han et al also reported that transfollicular delivery of drug molecules was enhanced by using a combination of liposomes and iontophoresis (Han et al, 2005;Han et al, 2004). In those reports, the intrafollicular delivery of small fluorescent drug molecules was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that during the first hair cycle of the normal rat skin, the sebaceous glands continually developed in the anagen and attained its fully development at catagen [ 9 ]. This development pattern of sebaceous glands of rat skin was repeated in our study, with the sizes of the sebaceous glands obviously increasing in the transition from anagen to catagen and holding steady in catagen and telogen.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that PDT using 5‐aminolevulinic acid (5‐ALA) induced hair follicle damage and inhibited the hair cycle in Sprague–Dawley rats. However, the detailed nature and results of hair damage were not well described . Grossman et al reported in their pilot study that PDT achieved more than 50% hair removal in 11 subjects and persisted for 6 months .…”
Section: Introductionmentioning
confidence: 99%